The protective role of caffeic acid on bovine mammary epithelial cells and the inhibition of growth and biofilm formation of Gram-negative bacteria isolated from clinical mastitis milk - Tianle Xu; Tianle Xu; Hao Zhu; Run Liu; Xinyue Wu; Guangjun Chang; Yi Yang; Zhangping Yang; Zhangping Yang (Frontiers in Immunology, 2022)
As a first-line barrier against bacterial infection of mammary tissues, bovine mammary epithelial cells (bMECs) are generally believed to be involved in the immune response due to exogenous stress. Due to the escalating crisis of antibiotic resistance, there is an urgent need for new strategies to combat pathogenic bacteria-infected bovine mastitis. In this study, isolated bMECs and Institute of Cancer Research (ICR) mice were used for Escherichia coli infection and caffeic acid (CA) pretreatment experiments in vitro and in vivo. The inhibitory effect of CA on bacterial growth and biofilm formation was also demonstrated with bacteria strains isolated from mastitis-infected milk. It was demonstrated that CA supplementation prohibits the growth of the predominant strains of bacteria isolated from clinical bovine mastitis milk samples. CA was found to disrupt the biofilm formation of E. coli B1 in a sub-minimum inhibitory concentration (sub-MIC) and inhibited the adherence property of E. coli on bMECs by decreasing the staining of bacteria on cell surfaces in vitro. In addition, CA was found to attenuate proinflammatory and oxidative responses in cells infected with E. coli. The pretreatment of bMECs with CA also restored altered lipid homeostasis caused by E. coli stimulation. The protective role of CA was further confirmed via the administration of CA in mice followed by representative Gram-negative bacterial infection. Collectively, these findings highlight the potential of CA to mediate Gram-negative infections and indicate that it has the potential to be developed as a novel antibacterial drug.